NUMERICAL PREDICTIONS ON FLOW AND HEAT TRANSFER IN HEAT EXCHANGER TUBE EQUIPPED WITH VARIOUS FLOW ATTACK ANGLES OF INCLINED-WAVY SURFACE - Withada Jedsadaratanachai; Amnart Boonloia (My University, 2018)
A premiere free-access and peer-reviewed frontier journal site, serving the needs of the thermal-fluids community. See the latest research or submit an article. Quickly share your research with the global thermal-fluids community, for increased citations and impact at no cost.
Keywords: Thermal fluids; Frontier; Thermal science; Heat Transfer and Optimization